Classic Insolvency Prediction Models Tested On Romanian Insurance Companies - Oniga, Alexandra (European Scientific Journal, ESJ, 2016)
This paper aims to analyse the applicability of classical bankruptcy prediction models for the Romanian insurance companies. Using four models, the Altman model, the Z-factor model, the Springate model and the model used to determine insolvency probability for the emerging markets we have conducted a study to see if they apply to Romanian insurance companies’ financial statements for the years between 2011 and 2013. We will present each model separately, analysing the indicators that led to the obtained results. In the end, we will combine the results to establish the applicability of these models to the Romanian insurance sector.